12c + 8t = 34
10c + 7t = 29
Equation 1 is in the correct format.
Equation 2 is in the correct format.
10c + 7t = 29
10c + 7t - 7t = 29 - 7t
10c = 29 - 7t
10c | |
10 |
= |
29 - 7t |
10 |
c = | 29 - 7t |
10 |
12(c) + 8t = 34
12 * ((29 - 7t)/10) + 8t = 34
((348 - 84t)/10) + 8t = 34
10 * (((348 - 84t)/10) + 8t = 34)
10 * (((348 - 84t)/10) + 8t = 34)
348 - 84t + 80t = 340
-84t + 80t = 340 - 348
-4t = -8
-4t | |
-4 |
= |
-8 |
-4 |
t = | -8 |
-4 |
t = 2
12c + 8(2) = 34
12c + 16 = 34
12c = 34 - 16
12c = 18
12c | |
12 |
= |
18 |
12 |
c = | 18 |
12 |
c = 1.5
Math is always fascinating! Have you noticed? On the path to discovering the ultimate mysteries of math, we move forward with small steps.